Нормирование параметров разгона легкового автомобиля - Волков, Владимир Петрович; Рабинович, Э. Х.; Зуев, В. А.; Зыбцев, Ю. В. (НТУ "ХПИ", 2015)
В статье обоснован выбор метода расчета нормативов времени разгона автомобилей при дорожном диагностировании с эмпирическими поправками, отражающими изменение конфигурации кривой крутящего момента при разгоне на разных передачах: снижение максимального крутящего момента и смещение его частоты вдоль оси частот вращения коленчатого вала в зависимости от передаточного числа включенной передачи в трансмиссии, а также увеличение крутизны ветвей этой кривой в зависимости от возраста или наработки двигателя.

The theory of internal combustion engines do not provide a simple way to calculate the change in the shape of the torque curve as a function of acceleration, so it is difficult to set reference values of the acceleration and process duration for a car diagnostics on a inertia dyno stand, as well as on the road. In the article the method for calculating the reference values of car acceleration parameters on different gears with empirical corrections to reflect the change in the torque curve configuration as a function of the acceleration is proposed. The K1 correction factor takes into account the decrease in torque according to the acceleration, which is approximately described by reduction ratio of the engaged gear in the transmission.
The calculating of reference values for car acceleration time
Keywords: время; крутящий момент; частота; смещение; эксперимент; расчет; поправки; acceleration time; torque; maximum frequency; reduction; displacement